2019
DOI: 10.1007/s40618-019-01138-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between biochemical control and comorbidities in patients with acromegaly: an Italian longitudinal retrospective chart review study

Abstract: Purpose Achieving biochemical control (normalization of insulin-like growth factor-1 [IGF-1] and growth hormone [GH]) is a key goal in acromegaly management. However, IGF-1 and GH fluctuate over time. The true potential impact of time-varying biochemical control status on comorbidities is unclear and relies on multiple, longitudinal IGF-1 and GH measurements. This study assessed the association between time-varying biochemical control status and onset of selected comorbidities in patients with acromegaly. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The information on health services utilization seems to indicate the potential for improved management of acromegaly. Previous studies have also consistently demonstrated that effective biochemical control of IGF-1 can help mitigate or reduce the effects of these comorbid conditions (as well as the acromegaly itself) and improve symptoms [32][33][34]. This could translate into ramifications for patterns of care implementation, intensity of care, and overall health expenditures.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…The information on health services utilization seems to indicate the potential for improved management of acromegaly. Previous studies have also consistently demonstrated that effective biochemical control of IGF-1 can help mitigate or reduce the effects of these comorbid conditions (as well as the acromegaly itself) and improve symptoms [32][33][34]. This could translate into ramifications for patterns of care implementation, intensity of care, and overall health expenditures.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…A retrospective study of 150 patients treated at a single center for a median of 10.4 years [ 22 ] assessed treatment and disease control impact on acromegaly comorbidities. Biochemical control, assessed only by a random growth hormone (GH) level < 2.5 μg/L, was associated with a lower hazard ratio (HR) of developing DM (HR 0.36; 95% CI 0.15, 0.83; p = 0.017) as well as cardiovascular system disorders overall (HR 0.54; 95% CI 0.31, 0.93; p = 0.027) compared to those not controlled.…”
Section: Presentation Comorbidities and Mortalitymentioning
confidence: 99%
“…Biochemical control, assessed only by a random growth hormone (GH) level < 2.5 μg/L, was associated with a lower hazard ratio (HR) of developing DM (HR 0.36; 95% CI 0.15, 0.83; p = 0.017) as well as cardiovascular system disorders overall (HR 0.54; 95% CI 0.31, 0.93; p = 0.027) compared to those not controlled. However, the risks of developing arterial hypertension and myocardial hypertrophy were not different [ 22 ]. An increased risk of arthropathy was also noted (HR 1.68; 95% CI 1.04, 2.71; p = 0.032), suggesting that, once established, structural changes are less likely to be influenced by biochemical control.…”
Section: Presentation Comorbidities and Mortalitymentioning
confidence: 99%
“…As the morbidity and mortality rate in acromegaly is significantly associated with IGF-1 and GH level, the aim of medical therapy is to ensure target IGF-1 level within age- and gender-specific normal ranges and to lower and normalize GH levels ( 1 4 ). Biochemical control of acromegaly assessed by a random GH level <2.5 µg/L in a recently published longitudinal study was associated with a significantly lower risk of developing diabetes mellitus as well as cardiovascular system disorders overall compared to those not controlled ( 5 ).…”
Section: Introductionmentioning
confidence: 99%